2005
DOI: 10.5551/jat.12.149
|View full text |Cite
|
Sign up to set email alerts
|

HMG-CoA Reductase Inhibitors Suppress the Development and Progression of Carotid Artery Intimal-medial Thickening in Hypercholesterolemic Type 2 Diabetic Patients

Abstract: We reported previously that 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (RIs) suppressed in vitro oxidized-low density lipoprotein-induced macrophage growth. To elucidate whether HMG-CoA RIs have anti-atherogenic effects separate from their cholesterol-lowering effect, total plasma levels of cholesterol in patients with type 2 diabetes mellitus (type 2 DM) and hypercholesterolemia were reduced to normal by one-year treatment with HMG-CoA RIs and intimal-medial thickness (IMT) of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…Among the different parameters analyzed, cholesterol and glucose values were the only ones showing a significant difference between C and T1 and T2 subjects. No clear explanation could be offered about the lower levels of cholesterol in T2 subjects as results have been reported in literature showing high cholesterol levels in T2 unless therapeutically controlled 18, 19. Although other authors have shown significantly high blood levels of CRP in diabetic patients,20 this study showed no significant difference from the control.…”
Section: Discussioncontrasting
confidence: 56%
“…Among the different parameters analyzed, cholesterol and glucose values were the only ones showing a significant difference between C and T1 and T2 subjects. No clear explanation could be offered about the lower levels of cholesterol in T2 subjects as results have been reported in literature showing high cholesterol levels in T2 unless therapeutically controlled 18, 19. Although other authors have shown significantly high blood levels of CRP in diabetic patients,20 this study showed no significant difference from the control.…”
Section: Discussioncontrasting
confidence: 56%
“…Statins effectively reduce cardiovascular end points in type 2 diabetes (3). Regarding surrogate markers of atherosclerosis in type 2 diabetes, statins improve endothelial dysfunction (4,5) and reduce markers of endothelial activation and inflammation (6 -8), progression of intima-media thickness (9), and augmentation index (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 11 studies were included in our meta-analysis. 8,10,18-25 Takahashi et al 21 had 2 groups with different statin therapy regimens compared to placebo group. For the purpose of this meta-analysis, these 2 groups were treated as separate studies.…”
Section: Literature Searchmentioning
confidence: 99%